GOD NEVER ENCOUNTERS US OUTSIDE OF OUR HISTORICITIES: IN CONVERSATION WITH SIMONMARY ASESE AIHIOKHAI (Hekima Review, 2023)
In this interview with the literary conversationist Chibueze Darlington Anuonye, the University of Portland’s Associate Professor of Systematic Theology, SimonMary Asese Aihiokhai talks about the intersectionality of culture (Africa), sexuality, the environment and gender in Christian theology. Starting with a focus on the impacts of the work of the late Kenyan theologian Teresia Mbari Hinga on centering African humanity and religion, the conversation highlights how colonialism and patriarchy undermine both indigenous African cultures and the Christian religion.